The Problem of Regional Identity in Vorpommern. - Alms, Judith Marie (Jihočeská univerzita, 2020)
The thesis assesses the influence of a regional development project on regional identity and vice versa. It is carried out on a project in the historic region Vorpommern in the north-east of Germany. The concept of regional identity by Anssi Palais is adopted. The qualitative case study on a development project in the district Peenetal/Loitz works with methods of grounded theory.
The Problem of Regional Identity in Vorpommern.
Keywords: regional development; regional identity; Anssi Paasi; Vorpommern; Western Pomerania; project management; rural sociology; Loitz; grounded theory; case study; regional development; regional identity; Anssi Paasi; Vorpommern; Western Pomerania; project management; rural sociology; Loitz; grounded theory; case study